Efeito de substratos alternativos no cultivo de Pleurotus spp.: novos métodos e perspectivas - Sousa , Flavia Helena Aires (2024)
The genus Pleurotus includes more than 200 saprophytic species, making it one of the world's best-known groups of edible mushrooms in the world. These fungi are recognized for their high capacity to synthesize enzymes, remarkable climatic adaptability, and ability to grow and develop on multiple lignocellulosic substrates, due to their production of lignolytic enzymes and capacity for the bioconversion of agro-industrial waste. However, there are still many gaps regarding the functionalities and benefits of these mushrooms. Therefore, this dissertation presents different perspectives on the genus. First, a comprehensive review of Pleurotus cultivation in Brazil over the last 30 years is provided, indicating the main discoveries related to commercial production in the country. In the second chapter, the potential of a culture medium based on wine seized by the Federal Revenue Service was investigated, using a new methodology for measuring the mycelial growth of the species Pleurotus ostreatus. The results presented in this study demonstrate that T1 was the most effective in promoting mycelial growth, followed by TC, T2, and T3 (in which there was no growth). Furthermore, when the two growth measurement methodologies were evaluated, it was found that the newly proposed methodology, called quadratic growth (QG), is more appropriate for monitoring growth because it accounts for the total area occupied, without averaging in the evaluations. For the third chapter, the use of discarded corn was analyzed as an alternative substrate for the cultivation of different species of Pleurotus, demonstrating the potential of this residue in the degradation of the substrate. In this study, all species evaluated demonstrated excellent productivity without the addition of supplements. Biological efficiency ranged from 47 (P. eryngii) to 76.4 (P. columbinus). The discarded corn substrate proved to be suitable for the cultivation of the analyzed mushroom species, offering a simple and economical solution for the use of lost or seized corn. Finally, the occurrence of Pleurotus cystidiosus in a new host for the Brazilian Amazon is reported, marking the first time that this species has been recorded in the cupuaçu root. This research includes a morphological and ecological description of the species, demonstrating that it was possible to identify the material through these indices. The results presented in this dissertation contribute to the expansion of knowledge about the cultivation of Pleurotus, suggesting new sustainable strategies.